Bioinspired hierarchical porous tough adhesive to promote sealing of high-pressure bleeding - Yinghao Li; Dongling Xiao; Weixi Yan; Meilin Jiang; Ju Tan; Zhongliang Qin; Jingting Zhou; Yue Sun; Mingcan Yang; Guanyuan Yang; Yawei Gu; Yong Liu; et al. (Bioactive Materials)
Timely and stable sealing of uncontrolled high-pressure hemorrhage in emergency situations outside surgical units remains a major clinical challenge, contributing to the high mortality rate associated with trauma. The currently widely used hemostatic bioadhesives are ineffective for hemorrhage from major arteries and the heart due to the absence of biologically compatible flexible structures capable of simultaneously ensuring conformal tough adhesion and biomechanical support. Here, inspired by the principle of chromatin assembly, we present a tissue-conformable tough matrix for robust sealing of severe bleeding. This hierarchical matrix is fabricated through a phase separation process, which involves the in-situ formation of nanoporous aggregates within a microporous double-network (DN) matrix. The dispersed aggregates disrupt the rigid physical crosslinking of the original DN matrix and function as a dissipative component, enabling the aggregate-based DN (aggDN) matrix to efficiently dissipate energy during stress and achieve improved conformal attachment to soft tissues. Subsequently, pre-activated bridging polymers facilitate rapid interfacial bonding between the matrix and tissue surfaces. They synergistically withstand considerable hydraulic pressure of approximately 700 mmHg and demonstrate exceptional tissue adhesion and sealing in rat cardiac and canine aortic hemorrhages, outperforming the commercially available bioadhesives. Our findings present a promising biomimetic strategy for engineering biomechanically compatible and tough adhesive hydrogels, facilitating prompt and effective treatment of hemorrhagic wounds.